Issues and Perspectives in Designing Clinical Trials for Negative Symptoms in Schizophrenia: Consensus Statements. Issue 1 (15th February 2020) - Marder, Stephen R; Davidson, Michael; Zaragoza, Silvia; Kott, Alan; Khan, Anzalee; Wang, Xingmei; Velligan, Dawn I; Umbricht, Daniel; Luthringer, Remy; Daniel, David
Abstract: Individuals from academia, the pharmaceutical industry, and regulators reevaluated earlier recommendations for the design of clinical trials for negative symptoms based on data from recent large trials. A session in February, 2018 at the International Society of CNS Clinical Trails and Methodology (ISCTM) annual meeting reviewed results from selected trials that reported findings between 2013 and 2018. The group reached a consensus on prior recommendations that should be reconsidered in future trials which included: (1) How can placebo effects be minimized? (2) Should global measures of negative symptoms be included? (3) Should a new drug targeting negative symptoms be tested in a monotherapy design or in an add-on design? (4) Can new information from negative symptom trials inform the selection of clinical outcome assessments (COA's) for future trials? For each of these issues new data was evaluated, discussed by the group, and in some cases the earlier recommendations were revised.